Development of Intermediate moisture product from wild FIG - lAKSHMI E. JAYACHANDRAN NEETHISH VARGHESE; Dr. Santhi Mary Mathew (Guide) (Tavanur 2012 Department of Post Harvest Technology Technol ogy and Agricultural Processing)
Development of Intermediate moisture product from wild FIG
Development of Intermediate moisture product from wild FIG